Correlation of body mass index and physical activity with serum uric acid levels: A Cross-Sectional Study among Medical Students - Shaula Arabia; Arif Rahman; Yanuarita Tursinawati (Jurnal Ilmiah Kesehatan Sandi Husada, 2026)
Introduction: Hyperuricemia is increasingly recognized as an early marker of metabolic disturbance among young adults. Body Mass Index (BMI) and physical activity are modifiable determinants that may influence serum uric acid levels, particularly in medical students who are exposed to sedentary academic routines and irregular lifestyle patterns. This study aimed to examine the association between BMI and physical activity levels with serum uric acid levels among medical students at Muhammadiyah University of Semarang. Research Methodology: An analytical observational study with a cross-sectional design was conducted in October 2025 involving 62 medical students selected through purposive sampling. BMI was calculated from measured weight and height; physical activity was assessed using the International Physical Activity Questionnaire–Short Form (IPAQ-SF); and serum uric acid levels were measured by capillary blood analysis. Data were analyzed using descriptive statistics, Spearman’s rank correlation test, and multivariable linear regression with a significance level of α = 0.05. Results: Most respondents had normal BMI (46.8%), high physical activity levels (53.2%), and normal uric acid levels (67.7%). Significant associations were found between BMI and serum uric acid (r = −0.286; p = 0.024) and between physical activity and serum uric acid (r = 0.271; p = 0.033). After adjustment for age and sex, both BMI (β = −0.254; p = 0.031) and physical activity (β = 0.236; p = 0.039) remained independently associated with uric acid levels. Conclusion: BMI and physical activity are significant determinants of serum uric acid levels in early adulthood. These findings support early metabolic screening and lifestyle-based interventions within university settings to prevent future cardiometabolic complications.